Pengaruh Struktur Kepemilikan Terhadap Transaksi Pihak Berelasi - Supatmi Supatmi; Krisvalenta Wukirasih (Owner : Riset dan Jurnal Akuntansi, 2022)
Related party transaction in some circumstances can create opportunities be detrimental to the minority (non-controlling) stakeholders and provide benefit to the majority (controlling) shareholders. Therefore, this study aims to find empirical evidence of the effect of ownership structure on related party transactions. Ownership structures are measured by family ownership, foreign ownership, blockholder ownership, and management ownership. Meanwhile, related party transactions are measured by related party transactions in asset and related party transactions in liability. The research samples are 128 companies in the manufacturing industry which are listed on the Indonesia Stock Exchange (IDX) period 2018 – 2020. This research uses quantitative methods with analysis technique uses panel data regression with the Eviews program. The study result that the higher the blockholder ownership, the more companies carried out related party transactions, both assets and liabilities. On the other side, the higher the management's ownership, the less the company conducts related party transactions, both assets and liabilities. Meanwhile, family ownership has a positive effect on related party transactions in assets and foreign ownership has a positive effect on related party transactions in liabilities. The research findings are in line with agency theory that concentrated ownership tends to encourage companies to conduct related party transactions.